Detection of the human endogenous retrovirus ERV3-encoded Env-protein in human tissues using antibody-based proteomics. (January 2014) - Fei, Chen; Atterby, Christina; Edqvist, Per-Henrik; Pontén, Fredrik; Zhang, Wei Wei; Larsson, Erik; Ryan, Frank P
Objectives: There is growing evidence to suggest that human endogenous retroviruses (HERVs) have contributed to human evolution, being expressed in development, normal physiology and disease. A key difficulty in the scientific evaluation of this potential viral contribution is the accurate demonstration of virally expressed protein in specific human cells and tissues. In this study, we have adopted the endogenous retrovirus, ERV3, as our test model in developing a reliable high-capacity methodology for the expression of such endogenous retrovirus-coded protein. Design: Two affinity-purified polyclonal antibodies to ERV3 Env-encoded protein were generated to detect the corresponding protein expression pattern in specific human cells, tissues and organs. Participants: Sampling included normal tissues from 144 individuals ranging from childhood to old age. This included more than forty different tissues and organs and some 216 different cancer tissues representing the twenty commonest forms of human cancer. Setting: The Rudbeck Laboratory, Uppsala University and Uppsala University Hospital, Uppsala, Sweden. Main Outcome Measures: The potential expression at likely physiological level of the ERV3Env encoded protein in a wide range of human cells, tissues and organs. Results: We found that ERV3 encoded Env protein is expressed at substantive levels in placenta, testis, adrenal gland, corpus luteum, Fallopian tubes, sebaceous glands, astrocytes, bronchial epithelium and the ducts of the salivary glands. Substantive expression was also seen in a variety of epithelial cells as well as cells known to undergo fusion in inflammation and in normal physiology, including fused macrophages, myocardium and striated muscle. This contrasted strongly with the low levels expressed in other tissues types. These findings suggest that this virus plays a significant role in human physiology and may also play a possible role in disease. Conclusion: This technique can now be extended to the study of other HERV genomes within the human chromosomes that may have contributed to human evolution, physiology and disease.